2018
DOI: 10.21511/ppm.16(2).2018.36
|View full text |Cite
|
Sign up to set email alerts
|

Company characteristics and risk management disclosure: empirical study of manufacturing companies listed on the Indonesia stock exchange

Abstract: This research aims to obtain empirical evidence on the effect of company characteritics on risk management disclosure (RMD) from the annual reports of manufacturing companies. The sample consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2010–2012. The total sample included 72 companies with three years observation and the examined firms reached 216. Results indicate that independent variables (firm size, profitability, leverage, public ownership, management owne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
5
1
3
Order By: Relevance
“…Pada penelitian terdahulu menyatakan bahwa keberadaan CEO wanita maupun Female CFO akan menurunkan tingkat manajemen laba perusahaan (Gavious et al, 2012). Sedangkan keberadaan wanita tidak berkaitan dengan manajemen laba pada perusahaan (Soebyakto et al, 2018). Selain itu, hampir semua perusahaan melakukan manajemen laba untuk menghindari kerugian yang terjadi pada perusahaan (Subekti, 2012); dan pertumbuhan pendapatan yang terjadi pada perusahaan akan mempengaruhi manajemen laba perusahaan (Suastini et al, 2016).…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Pada penelitian terdahulu menyatakan bahwa keberadaan CEO wanita maupun Female CFO akan menurunkan tingkat manajemen laba perusahaan (Gavious et al, 2012). Sedangkan keberadaan wanita tidak berkaitan dengan manajemen laba pada perusahaan (Soebyakto et al, 2018). Selain itu, hampir semua perusahaan melakukan manajemen laba untuk menghindari kerugian yang terjadi pada perusahaan (Subekti, 2012); dan pertumbuhan pendapatan yang terjadi pada perusahaan akan mempengaruhi manajemen laba perusahaan (Suastini et al, 2016).…”
Section: Pendahuluanunclassified
“…Keberadaan wanita dalam jajaran komisaris tidak berkaitan dengan praktek manajemen laba pada perusahaan (Soebyakto et al, 2018). Pada penelitian Krishnan dan Parsons (2008); Emadi dan Mansour (2015) menunjukkan dengan adanya keberadaan wanita pada posisi manajemen puncak dan dengan jumlah yang lebih banyak akan berdampak pada earnings management perusahaan, maka hipotesis penilitian sebagai beikut: H3: Female Board of Commisioners berpengaruh terhadap earnings management.…”
Section: Pengembangan Hipotesisunclassified
See 1 more Smart Citation
“…Abdul Rahman, Mustapa, & Alshira'h (2020) on companies in Jordan that large companies and industrial-type companies tend to disclose broader risk information. The same argument was also established in Soebyakto, Mukhtaruddin, Relasari, & Sinulingga (2018) after analyzing the manufacturing companies listed on the Indonesia Stock Exchange (IDX) 2010-2012 and found that firm size significantly affected risk management disclosure measured by financial, operational, power, processing, integrity, and strategic risks.…”
Section: Template Of Jurnal Economiamentioning
confidence: 69%
“…Our results may differ if Indonesia has more female CEOs. Soebyakto et al (2018) also document that female CEOs and CFOs do not affect managerial practice decisions. Similarly, Hili & Affes (2012) suggest that feminism representation in firms' managerial positions and governance does not affect earnings management.…”
Section: Hypothesis Testingmentioning
confidence: 98%